GAMBARAN KARAKTERISTIK DAN PRAKTIK PENCEGAHAN COVID-19 PADA MAHASISWA UNIVERSITAS DIPONEGORO SEMARANG - Maurizka Viera Chairunissa; Mateus Sakundarno Adi; Moh Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Abstract: Kementerian Pendidikan dan Kebudayaan announced that face-to-face lectures during the COVID-19 pandemic would begin in January 2021. Diponegoro University as the campus with the largest number of students in Semarang must prepare strict health protocols. The application of good COVID-19 prevention practices to students is needed to reduce the rate of transmission of the virus that causes COVID-19. The purpose of this study is to describe the characteristics of respondents in the form of gender, type of study, total monthly expenditure, and completeness of access to information with the COVID-19 prevention practices among Diponegoro University students in Semarang. Sampling was chosen non-randomly by using a quota sampling technique. Data was collected using a questionnaire via Google Form. Data was analysed using univariate analysis to describe the frequency distribution of the research variables, as well as bivariate analysis with 2x2 cross tabulations to describe the characteristics of respondents with prevention practices related to COVID-19. The number of samples collected was 528 respondents. The results showed that 275 respondents (52.2%) had good COVID-19 prevention practices. Respondents who had good practices were more often found in female respondents (60.6%), studied in health major (64.5%), had high total expenditures per month (56.9%), and sufficient access to information related to COVID -19 (59.7%).